Natural versus synthetic curcuminoids as photosensitizers: Photobleaching and antimicrobial photodynamic therapy evaluation - Melo, Nicolas Junhiti de; Tovar, Johan S.D.; Dovigo, Lívia Nordi [UNESP]; Dias, Lucas D.; Bagnato, Vanderlei Salvador; Inada, Natalia Mayumi (Elsevier, 2023)
Antimicrobial photodynamic therapy (aPDT) has been studied as an alternative to combat bacterial resistance to the commonly used antibiotics. aPDT requires the use of a photosensitizer and curcumin is one of the more promising, though the usage of natural curcumin can be inconsistent in certain biomedical uses due to differences in soil condition and turmeric age, besides a large quantity of the plant is necessary to obtain useful amounts of the actual molecule. As such, a synthetic analogue is preferred as it is pure, and its components are better characterized. The present work studied photophysical differences in both natural and synthetic curcumin using photobleaching experiments and searched for whether differences existed in aPDT studies against Staphylococcus aureus. The results showed a faster O2 consumption and a singlet oxygen's generation rate lower by the synthetic curcumin, in comparison with the natural derivative. However, no statistical difference was observed when inactivating S. aureus and these results were following a concentration-based pattern. Thus, the use of synthetic curcumin is indicated, as it can be obtained in controlled amounts and with less environmental impact. Although there are small changes in a photophysical context comparing natural versus synthetic curcumins, we did not observe statistical differences in the photoinactivation of S.aureus bacteria, and reproducibility in biomedical contexts is better achieved with the synthetic analogue.
Keywords: Antimicrobial photodynamic therapy; Curcumin; Photobleaching; Photochemotherapy; Photodynamic therapy